Artikel Review Fitokimia: Efektivitas Infusa sebagai Metode Ekstraksi - cha, charles06; Nisful lailatun nadiroh (Jurnal Farmasi Sains dan Teknologi, 2025)
Extraction is a fundamental process in isolating bioactive compounds from natural materials that is crucial for the development of pharmaceutical, food, and cosmetic products. Infusion as one of the conventional extraction methods uses water solvent at approximately 90°C for 15 minutes which is widely used due to its simplicity, does not require complex equipment, is economical, and is capable of extracting polar compounds effectively. This review aims to comprehensively examine the working principles of the infusion method based on the diffusion process of bioactive compounds, factors affecting extraction effectiveness, advantages and disadvantages of the method, applications on various groups of phytochemical compounds, and recent innovations in method modification. The review method was conducted through literature searches from Google Scholar, Garuda, and PubMed using keywords "infusion", "extraction method", "infusion effectiveness", "diffusion process", and "hot method" in publications from 2015-2025. The review results show that extraction yields vary between 2.92% to 38.65% with good standards of 10-15%, influenced by phytochemical characteristics of plants, anatomical structure, thermal stability of compounds, extraction time, and sample-solvent ratio. The infusion method is effective for extracting polar compounds such as tannins, phenolics, flavonoid glycosides, and heat-stable alkaloids, but requires modification for semipolar terpenoids. Although modern methods such as UAE and MAE produce higher yields, infusion remains relevant in Indonesia's herbal industry with more than 15,000 herbal products registered with BPOM due to short extraction time, preventing degradation of thermolabile compounds, and producing products easily accepted by the community, despite having limitations in extract stability with shelf life of less than 24 hours. Future prospects for infusion method development lie in integration with ultrasonic technology, use of Natural Deep Eutectic Solvent (NADES) as green solvent, and optimization of Response Surface Methodology (RSM) to improve efficiency while maintaining principles of simplicity and sustainability supporting standardization of standardized herbal medicines and phytopharmaceuticals according to BPOM regulations.